2002
DOI: 10.1007/s00167-001-0272-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone bruise in the acutely injured knee

Abstract: We used MRI to study the lesions in a consecutive group of 64 patients with an acute trauma of the knee and normal plain radiography during the winter season. Bone bruise was present in 35 of the patients, and these were referred to subsequent MRI 4 and 12 months later. After 4 months bone bruise was still present in 69% of the patients and after 12 months in 12%. Soft tissue lesions, for example, lesion in the meniscus, ACL rupture, or MCL lesion was present in 94% of the patients with bone bruise. Interobser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 20 publications
6
72
1
2
Order By: Relevance
“…Our present study also showed that most BMELs had resolved at 6 months after ACL reconstruction and only 22.2% remained at that time-point, and even a smaller portion (6.5%) could be seen at 2 years followup MR imaging. The rapid resolution of BMELs over time in this study was similar to what other studies have reported (39,40). Nine new BMELs in six injured knees (16.2%) were detected in the course of the 2-year followup (3 at 6-month, 4 at 1-year and 2 at 2-year).…”
Section: Discussionsupporting
confidence: 92%
“…Our present study also showed that most BMELs had resolved at 6 months after ACL reconstruction and only 22.2% remained at that time-point, and even a smaller portion (6.5%) could be seen at 2 years followup MR imaging. The rapid resolution of BMELs over time in this study was similar to what other studies have reported (39,40). Nine new BMELs in six injured knees (16.2%) were detected in the course of the 2-year followup (3 at 6-month, 4 at 1-year and 2 at 2-year).…”
Section: Discussionsupporting
confidence: 92%
“…The ill-defined low T1 and corresponding high T2 signal on MRI is similar to stress reactions, but can be differentiated by patient history, physical examination findings (overlying ecchymosis), surrounding soft tissue edema on MRI, and location of the marrow abnormality [14]. Extrapolating from a study of knee contusion marrow edema, marrow signal abnormality in hip contusions may be seen as early as 1 h, and more reliably at 6 h, post injury [15] and may persist up to 4 months, as was seen in nearly 70 % of patients in another study [16].…”
Section: Contusionmentioning
confidence: 94%
“…A recent study by Boks et al suggests that, contrary to expectations, reticular post traumatic BMLs are not associated with increased pain severity in posttraumatic knees 25 . Simple post-traumatic BMLs without involvement of the articular surface are thus likely to be benign occurrences 26,27 . As such, post-traumatic BMLs generally resolve without sequelae within 6-12 months following the injury, though new BMLs have been shown to develop in approximately one-third of ACL-injured knees over the first two years post-injury [26][27][28] .…”
Section: Post-traumatic Bone Marrow Lesionsmentioning
confidence: 99%